Mechanisms of subzero growth in the cryophile Planococcus halocryophilus determined through proteomic analysis. (13th October 2017) - Raymond‐Bouchard, Isabelle; Chourey, Karuna; Altshuler, Ianina; Iyer, Ramsunder; Hettich, Robert L.; Whyte, Lyle G.
Summary: The eurypsychrophilic bacterium Planococcus halocryophilus is capable of growth down to −15°C, making it ideal for studying adaptations to subzero growth. To increase our understanding of the mechanisms and pathways important for subzero growth, we performed proteomics on P . halocryophilus grown at 23°C, 23°C with 12% w/v NaCl and −10°C with 12% w/v NaCl. Many proteins with increased abundances at −10°C versus 23°C also increased at 23C‐salt versus 23°C, indicating a closely tied relationship between salt and cold stress adaptation. Processes which displayed the largest changes in protein abundance were peptidoglycan and fatty acid (FA) synthesis, translation processes, methylglyoxal metabolism, DNA repair and recombination, and protein and nucleotide turnover. We identified intriguing targets for further research at −10°C, including PlsX and KASII (FA metabolism), DD‐transpeptidase and MurB (peptidoglycan synthesis), glyoxalase family proteins (reactive electrophile response) and ribosome modifying enzymes (translation turnover). PemK/MazF may have a crucial role in translational reprogramming under cold conditions. At −10°C P . halocryophilus induces stress responses, uses resources efficiently, and carefully controls its growth and metabolism to maximize subzero survival. The present study identifies several mechanisms involved in subzero growth and enhances our understanding of cold adaptation.